2012
DOI: 10.1007/s10681-012-0651-y
|View full text |Cite
|
Sign up to set email alerts
|

A limited set of starch related genes explain several interrelated traits in potato

Abstract: To understand the molecular basis of potato starch related traits and the underlying starch biosynthesis and degradation, a Quantitative Trait Locus (QTL) analysis in combination with a candidate gene approach was performed. The diploid mapping population C 9 E, consisting of 249 individuals, was assayed over two consecutive years, for chipping colour, cold induced sweetening, starch content, starch granule size, starch gelling temperature, starch enthalpy, amylose content and degree of starch phosphorylation.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
69
1
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 55 publications
(77 citation statements)
references
References 41 publications
3
69
1
2
Order By: Relevance
“…The reduced phosphate content in potato starch have some secondary effects on its degradability, as the respective plants show a starch excess phenotype in leaves and a reduction in cold-sweetening in tubers. In a mapping study in potato, Pho 1a emerged as a candidate gene linked to starch gelling and starch granule size [47]. In another study, it was found that the antisense inhibition of isoamylase in potato induces massive numbers of small granules in tubers, suggesting that the debranching activity is necessary to prevent excessive granule initiation [48].…”
Section: Genetic Engineering Of Potato To Modify the Starch Granule Sizementioning
confidence: 99%
See 1 more Smart Citation
“…The reduced phosphate content in potato starch have some secondary effects on its degradability, as the respective plants show a starch excess phenotype in leaves and a reduction in cold-sweetening in tubers. In a mapping study in potato, Pho 1a emerged as a candidate gene linked to starch gelling and starch granule size [47]. In another study, it was found that the antisense inhibition of isoamylase in potato induces massive numbers of small granules in tubers, suggesting that the debranching activity is necessary to prevent excessive granule initiation [48].…”
Section: Genetic Engineering Of Potato To Modify the Starch Granule Sizementioning
confidence: 99%
“…The development of new methods in plant breeding that would circumvent these regulatory problems would be of greatly stimulated the development of novel starches [55]. The identification of genetic marker associated with starch properties and the exploitation of new mutations in tilling populations are other tools with great potential for uncovering key genes determining starch properties [47]. Another bottleneck to produce improved starches is associated with the difficulties in predicting beforehand the effect of a (trans) gene.…”
Section: Perspectives Of Gmo Starchesmentioning
confidence: 99%
“…Using the method of interval mapping of genomes in a population of diploid potatoes, it was shown that starch phosphorylation is regulated and/or controlled by five quantitative trait loci (QTL) on chromosomes 2, 5 and 9, and the content of amylose by six loci on chromosomes 2, 3, 5, 7 and 10. Similarly, loci controlling the starch grain size, the starch content of potato tuber and the temperature of starch gelatinization were discovered [45,46]. Many of the identified QTLs coincided by their localization with the known genes that encode the enzymes of starch biosynthesis, but, in addition, loci have also been discovered in which no one of the starch biosynthetic genes was previously mapped.…”
Section: Introductionmentioning
confidence: 98%
“…The development of new methods in plant breeding that would circumvent these regulatory problems would be of greatly stimulated the development of novel starches (Lusser et al, 2012). The identification of genetic marker associated with starch properties and exploitation of new mutations in tilling populations are other tools with great potential for uncovering key genes determining starch properties (Werij et al, 2012).…”
Section: Perspectives Of Gmo Starchesmentioning
confidence: 99%
“…Therefore, a better understanding of starch biosynthesis and key players in crop plants is necessary. To achieve this, identification of genetic marker associated with starch characteristics in crops (Werij et al, 2012) and new mutations in TILLING populations (Slade et al, 2012) provide tremendous potential gains. All in all, "green" and socially-acceptable approaches are required for starch bioengineering.…”
Section: Future Perspective -"Green" and Socially-acceptable Approachmentioning
confidence: 99%